Coseismic fault slip inversion of the 2013 Lushan Ms 7.0 earthquake based on the triangular dislocation model - HuRong Duan; JiaYing Chen; ShuangCheng Zhang; XiaoLong Wu; ZiMing Chu (Scientific Reports, 2022)
Abstract The 2013 Lushan Ms 7.0 earthquake occurred on the Longmenshan thrust tectonic zone, a typical blind reverse-fault type earthquake that caused the death of nearly 200 people. The investigation of the fault geometry and fault slip distribution of this earthquake is important for understanding the seismogenic tectonic type and seismic activity mechanism of the Longmenshan Fault Zone. In this paper, for the fault geometry of the Ms 7.0 earthquake in Lushan, the geometric parameters of the planar fault are inverted based on the rectangular dislocation model using GPS coseismic displacement data, and on this basis, a curved fault steeply-dipping on top and gently-dipping at depth is constructed by combining the aftershock distribution. The GPS and leveling data are used to invert the slip distribution of the curved fault for the Lushan Ms 7.0 earthquake. The results show that the fault is dominated by reverse slip with a small amount of sinistral rotation, and there is a peak slip zone with a maximum slip of 0.98 m, which corresponds to a depth of ~ 13.50 km, and the energy released is 1.05 × 1019 N/m with a moment magnitude of Mw 6.63. Compared with the planar rectangular dislocation model, the curved fault model constructed by using triangular dislocation elements can not only better approximate the fault slip, but also better explain the observed surface displacement, and the root mean square error of the GPS and leveling data fitting is reduced by 1.3 mm and 1.9 mm, respectively. Both the maximum slip and moment magnitude of the fault based on the inversion of the curved structure are slightly larger than the results based on the planar structure.